RNA polymerase II transcription factors H4TF-1 and H4TF-2 require metal to bind specific DNA sequences. - Dailey, L (1987)
Specific DNA-binding and in vitro transcription activities of H4TF-1 and H4TF-2 are inactivated by chelating agents. Binding activity is restored by addition of Zn2+, and H4TF-2 is also reactivated by Fe2+. In contrast, preformed factor-DNA complexes are resistant to chelators. Therefore, metal ions are a required component of the H4TF-1 and H4TF-2 DNA-binding domains.